An employer demand intelligence framework - Smalberger, Chamonix (Curtin University, 2013)
Employer demand intelligence is crucial to ensure accurate and reliable education, workforce and immigration related decisions are made. To date, current methods have been manually intensive and expensive — providing insufficient scope of information required to address such important economic implications. This research developed an Employer Demand Intelligence Framework (EDIF) to address detailed employer demand intelligence requirements. To further the EDIF’s functionality, a semi-automated Employer Demand Identification Tool (EDIT) was developed that continuously provide such intelligence.